2020
DOI: 10.21608/eajbsz.2020.105147
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Some Treatments for Coliform Infection in Chicken

Abstract: This work was designed to investigate the effect of yeast(Saccharomyces cerevisiae) and Sangrovit as natural feed additives on chicken production performance, some hematological parameters, some biochemical parameters, histopathological examination of (liver and kidney) and total coliform count of intestinal content in normal and experimentally infected chickens with E.coli O 78. A total of 120 unsexed one-day-old, broiler chickens (Cobb) were randomly assigned to 6 treatment groups each of 20 as follows: G1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…Administration of T-Nil Plus ® not alters the level of serum uric acid in broiler chicken. These results are in accordance with Mahmoud (14) ; Al-Afifi et al, (49) and Hasan et al (50) who said that administration of Saccharomyces cerevisiae wall not change the serum level of uric acid in chickens. Our results showed that birds treated with Synertox ® revealed non-significant changes of serum creatinine level at 1 st day post-treatment.…”
Section: Efficacy Of T-nil Plus® and Synertox® On Chickensupporting
confidence: 92%
“…Administration of T-Nil Plus ® not alters the level of serum uric acid in broiler chicken. These results are in accordance with Mahmoud (14) ; Al-Afifi et al, (49) and Hasan et al (50) who said that administration of Saccharomyces cerevisiae wall not change the serum level of uric acid in chickens. Our results showed that birds treated with Synertox ® revealed non-significant changes of serum creatinine level at 1 st day post-treatment.…”
Section: Efficacy Of T-nil Plus® and Synertox® On Chickensupporting
confidence: 92%